2014
DOI: 10.1371/journal.pone.0111306
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Influence of Pre-Operative C-Reactive Protein in Node-Negative Breast Cancer Patients

Abstract: The importance of inflammation is increasingly noticed in cancer. The aim of this study was to analyze the prognostic influence of pre-operative serum C-reactive protein (CRP) in a cohort of 148 lymph node-negative breast cancer patients. The prognostic significance of CRP level for disease-free survival (DFS), metastasis-free survival (MFS) and overall survival (OS) was evaluated using univariate and multivariate Cox regression, also including information on age at diagnosis, tumor size, tumor grade, estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 35 publications
(3 reference statements)
0
21
0
Order By: Relevance
“…In recent years, some studies have demonstrated the prognostic value of blood parameters and serum parameters, which are inexpensive, accurate, identified by easy method of detection and validated. Although underlying mechanism is unclear, increased pretreatment blood parameters and serum parameters have been confirmed to associate with prognosis of several cancers, such as neutrophil-to-lymphocyte ratio (NLR)17, 18, lymphocyte-to-monocyte ratio (LMR), monocyte count19, platelet-to-lymphocyte ratio (PLR)20, fibrinogen21 haptoglobin 22and C-reactive protein23. The serum levels of ALP and LDH are routine diagnostic tests in clinical laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies have demonstrated the prognostic value of blood parameters and serum parameters, which are inexpensive, accurate, identified by easy method of detection and validated. Although underlying mechanism is unclear, increased pretreatment blood parameters and serum parameters have been confirmed to associate with prognosis of several cancers, such as neutrophil-to-lymphocyte ratio (NLR)17, 18, lymphocyte-to-monocyte ratio (LMR), monocyte count19, platelet-to-lymphocyte ratio (PLR)20, fibrinogen21 haptoglobin 22and C-reactive protein23. The serum levels of ALP and LDH are routine diagnostic tests in clinical laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…But on gene expression analysis in a subgroup of 72 patients, they for first time highlighted no relation of circulating CRP with gene expression. Numerous epidemiological prospective studies proved CRP as a well-established independent prognostic marker in breast cancer [ 32 ]. Breast cancer survivors with the state of chronic inflammation are at risk of recurrence of the disease as well as metabolic disturbances and CVD.…”
Section: Crp As a Prognostic Predictor For Breast Cancermentioning
confidence: 99%
“…Although the prognostic impact of preoperative CRP has been reported (16,17), other studies have described controversial results (18)(19)(20). Thus, the present study aimed to evaluate the prognostic impact of preoperative CRP and IL-6 expression levels in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 92%
“…CRP, which was named for its capacity to precipitate C-polysaccharide of Streptococcus pneumoniae, is a sensitive and widely used inflammatory marker produced primarily in the liver, in response to IL-1, IL-6, tumor necrosis factor-α and IL-17 (7,8). CRP was reported to be associated with poor prognosis in nasopharyngeal (9), hepatocellular (10), pancreatic (11), colorectal (12), renal (13), urothelial (14) and prostate cancer (15), in addition to breast cancer (16,17). However, the association between CRP and the prognosis of patients with breast cancer remains controversial (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%